Asset Intelligence through Integration and Interoperability and Contemporary Vibration Engineering Technologies : proceedings of the 12th World Congress on Engineering Asset Management and the 13th International Conference on Vibration Engineering and Technology of Machinery /: proceedings of the 12th World Congress on Engineering Asset Management and the 13th International Conference on Vibration Engineering and Technology of Machinery. (2018) - Unknown
No abstract available